PROSPECTIVE TASKS OF DIRECTING MORAL AND RELIGIOUS VALUES TO A COMMON GOAL IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
In the article, the theoretical foundations of the study of the dialectical relationship between moral and religious values in the era of globalization, the dialectical analysis of the dialectical relationship between moral and religious values in the era of globalization, the problems and solutions of the future relationship of moral and religious values ​​in the era of globalization are studied. Also, the genesis of the concept of moral and religious values, scientific-conceptual bases are analyzed.